A descriptive and prognostic study of systemic sclerosis-associated myopathies. Issue 9 (3rd December 2008) - Ranque, B; Authier, F-J; Le-Guern, V; Pagnoux, C; Berezne, A; Allanore, Y; Launay, D; Hachulla, E; Kahan, A; Cabane, J; Gherardi, R; Guillevin, L; et al.
Abstract : Objectives: To describe the clinical characteristics and muscle pathological features of patients with systemic sclerosis (SSc) and myopathy and analyse their impact on muscle outcome. Methods: Thirty-five patients with myopathy and available muscle biopsy were restrospectively investigated from the charts of four hospital centres. Results: Twenty-six (74%) cases had diffuse SSc. The median time from SSc diagnosis was 5 years (range 0–23) at myopathy onset. The main myopathological features were mononuclear inflammation (63%), muscle atrophy (60%), necrosis (59%), regeneration (44%), fibrosis (24%) or microangiopathy (27%). After a median follow-up of 4.4 years, 24 patients (69%) showed complete or partial muscle remission. Only histological muscle inflammation was associated with good muscle prognosis in multivariate analysis (odds ratio 44.7, 95% CI 2.8 to 704.7). Patients without muscle inflammation had a poor response to corticosteroids (38% favourable response vs 90% in patients with inflammation). Conclusion: Muscle histopathology is critical in the therapeutic management of SSc-associated myopathy.